1991
DOI: 10.3168/jds.s0022-0302(91)78282-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somidobove Sustained Release Administration on the Lactation Performance of Dairy Cows

Abstract: Lactation performance was determined on 190 multiparous Holsteins from five herds supplemented with 0, 320, 640, or 960 mg of somidobove every 28 d. The experiment consisted of 21 d of pretreatment and treatment periods of various lengths, depending upon stage of lactation of animals at first administration. Somidobove beginning in early (28 to 45 d in milk), mid (111 to 166 d in milk), or late (166 to 334 d in milk) stages of lactation consisted of 9, 6, or 3 administrations. Milk and 3.5% FCM yields were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…The effect of Somidobove on production was cyclic and the production response was sustained only for the first 14 d of each 28-d treatment cycle. The production response in percentage and absolute terms was in the range of that observed in other studies with similar preparations of Somidobove in concentrate-fed cows (Oldenbroek et al 1989;Kim et al 1991;McGuffey et al 1991) or in cows on pasture supplemented with grain (Valentine et al 1990). The yield responses were slightly higher, on average, than those obtained in the only other long-term study undertaken in New Zealand with recombinant-derived bST (Hoogendoorn et al 1990).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The effect of Somidobove on production was cyclic and the production response was sustained only for the first 14 d of each 28-d treatment cycle. The production response in percentage and absolute terms was in the range of that observed in other studies with similar preparations of Somidobove in concentrate-fed cows (Oldenbroek et al 1989;Kim et al 1991;McGuffey et al 1991) or in cows on pasture supplemented with grain (Valentine et al 1990). The yield responses were slightly higher, on average, than those obtained in the only other long-term study undertaken in New Zealand with recombinant-derived bST (Hoogendoorn et al 1990).…”
Section: Discussionsupporting
confidence: 76%
“…around 3.0 kg d ' in cows fed pasture diets supplemented with grain (Valentine et al 1990). This was a similar level of response to that obtained with a similar bST preparation in concentrate-fed cows (Oldenbroek et al 1989;McGuffey et al 1991). The study reported below was carried out with a sustained release preparation of bST (Somidobove, at two doses) as used in other trials (Oldenbroek et al 1989;McGuffey et al 1990McGuffey et al , 1991Valentine et al 1990).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Asimov and Krouze in 1937 first demonstrated injections of pituitary extract increased milk production in dairy cows ( 1). Investigators since then have shown bovine somatotropin regulates metabolic processes resulting in more efficient milk synthesis, greater milk production and increases lean tissue synthesis (2)(3)(4). With the advancement in recombinant DNA technology, production and isolation of bovine somatotropin became commercially feasible.…”
Section: Introduction Foster and Leathermanmentioning
confidence: 98%
“…High circulating growth hormone (GH) concentrations in females result in decreased reproductive performance in mice , Thomas et al 2001, humans (Jadresic et al 1982) and livestock (McGuffey et al 1991, Downer et al 1993, Oldenbroek et al 1993, Esteban et al 1994, Buskirk et al 1996, Chapula et al 1996. It is still unclear whether elevated GH suppresses reproductive function directly or through an intermediary pathway.…”
Section: Introductionmentioning
confidence: 99%